1998
DOI: 10.1046/j.1365-2281.1998.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training, overtraining and baroreflex sensitivity in female athletes

Abstract: SummaryWe examined heavy training-induced changes in baroreflex sensirivity, plasma volume and resring heart rate and blood pressure variability in female endurance athletes. Nine athletes (experimental training group, ETG) increased intense training (70-90% Vo2maJ volume by 130% and low-intensity training «70% Vo2maJ volume by 100% during 6-9 weeks, whereas the corresponding increases in six control athletes (CG) were 5% and 10% respecrively. Maximal oxygen uptake (Vo2maJ in the ETG and CG did not change, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
(14 reference statements)
4
32
0
7
Order By: Relevance
“…By contrast, sympathetic modulation on the TPG was higher comparing to the RPG due to a greater increase in LF (8). The LF increase in the TPG is in accordance with previous studies that found higher values of this parameter in endurance athletes after performing an experimental high volume training program during 6-9 weeks (25). The increase in sympathetic modulation in the TPG is contrary to the lower LF and less training volumes in the RPG, this phenomenon, jointly with the decrease in autonomic adaptation of the TPG have been described in the literature for periods of high training load (10).…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, sympathetic modulation on the TPG was higher comparing to the RPG due to a greater increase in LF (8). The LF increase in the TPG is in accordance with previous studies that found higher values of this parameter in endurance athletes after performing an experimental high volume training program during 6-9 weeks (25). The increase in sympathetic modulation in the TPG is contrary to the lower LF and less training volumes in the RPG, this phenomenon, jointly with the decrease in autonomic adaptation of the TPG have been described in the literature for periods of high training load (10).…”
Section: Discussionsupporting
confidence: 92%
“…Quanto à hipótese da VFC não ter se alterado devido à pequena magnitude no aumento das cargas de treinamento em T1, em estudos nos quais houve aumentos consideráveis das cargas de treinamento, da ordem de até 100% do total treinado 13,14 , foram observadas mudanças significativas na VFC. Contudo, estudos recentes em que as alterações das cargas de treinamento não foram tão grandes, não encontraram alterações na VFC após períodos com cargas de treinamento diferentes, moderadas e altas ao longo da temporada esportiva 16,17 .…”
Section: Estresse Geralunclassified
“…Sendo assim, mudanças na modulação autonômica cardíaca aparentemente são percebidas apenas em situações em que atletas são submetidos a cargas de treinamento extremamente elevadas, de forma a levar os voluntários à exaustão 9,15 , o que nem sempre ocorre numa situação real de treinamento com finalidade competitiva, como nesta investigação, na qual o programa de treinamento foi concebido visando a participação em competição de nível nacional, e, não, no intuito de levar os voluntários a situações extremas de fadiga crônica. Outros estudos mostram, ainda, que ocorrem modificações na atuação simpática apenas em períodos curtos de tempo como adaptação ao treinamento, imediatamente seguintes às alterações na carga de exercícios 13,14,17 . No presente estudo as coletas foram realizadas em intervalos de quatro Tabela 1.…”
Section: Estresse Geralunclassified
See 1 more Smart Citation
“…Por exemplo, Lehmann, Foster e Keul [48] concluíram que a implantação de um programa de treinamento diminuiu a sensibilidade da glândula adrenal ao ACTH em atletas recreacionais. Isto poderia explicar alguns estudos que indicaram uma diminuição na liberação do cortisol em atletas em OT [4,49,84].…”
Section: ) Variações No Eixo Hipotálamo-hipófise-adrenal (Hha)unclassified